Hospital admissions from birth to early adolescence and early-life risk factors: the 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study Hospitalizações do nascimento ao início da adolescência e fatores de risco precoces: a visita de 11 anos da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993 - Ana M. B. Menezes; Ricardo B. Noal; Juraci A. Cesar; Pedro C. Hallal; Cora Luiza Araújo; Samuel C. Dumith; Fernando C. Barros; Cesar G. Victora (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this prospective analysis was to describe the cumulative incidence of hospital admissions in the first year of life and between 1 and 11 years of age and to explore associated factors. Hospital admissions were collected through regular monitoring in the first year of life, and through maternal report on admissions between 1 and 11 years. Analyses were stratified by sex and adjusted for confounding factors. 18.1% of children were hospitalized in the first year of life, and 30.7% between ages 1 and 11 years. Among boys, hospital admission in the first year was associated with low family income, paternal smoking during pregnancy, preterm delivery, and low birthweight. Among girls, in addition to the variables described for boys, black/mixed skin color was also a risk factor for hospital admission. For admissions between 1 and 11 years of age, low family income and gestational age > 37 weeks were found to be significant risk factors. Com o objetivo de descrever a incidência cumulativa de hospitalizações no primeiro ano de vida e entre 1-11 anos de idade, e identificar fatores de risco precoces, foi realizado um estudo de coorte de nascimento de 1993 a 2004-2005. As hospitalizações foram coletadas por meio de monitoramento hospitalar até 1 ano de idade, e relato das mães sobre internações ocorridas de 1-11 anos. As análises foram estratificadas por sexo e ajustadas para fatores de confusão. Os percentuais de hospitalizações de 0-1 ano e de 1-11 anos foram 18,1% e 30,7%, respectivamente. As variáveis associadas com internações de 0-1 ano em meninos foram: baixa renda familiar, tabagismo paterno na gestação, prematuridade e baixo peso ao nascer. No sexo feminino, além dos fatores de risco descritos entre os meninos, observou-se associação com cor da pele preta/parda. Quanto às hospitalizações de 1-11 anos, no sexo masculino, encontrou-se associação com baixa renda familiar e idade gestacional > 37 semanas.